Pathologic dislocation of the shoulder secondary to septic arthritis: a case report - Bagheri, Farshid (BioMed Central, 2009)
Septic arthritis of the shoulder is uncommon in adults, and complete dislocation of the glenohumeral joint following septic arthritis is extremely rare. We report a case of pathologic shoulder dislocation secondary to septic arthritis in an intravenous drug abuser.